The Effect of Unemployment and Population on the Poor Population of North Sumatra Province in 2001-2020 - Achmad; Avis; Mirnawati; Muhammad Nazly; Muammar Rinaldi (Outline Journal of Economic Studies, 2023)
This study aims to analyze the effect of unemployment and population on poverty levels in North Sumatra Province from 2001 to 2020. The data used in this study are sourced from the Central Sumatra Statistics Agency and multiple linear regression analysis is used to analyze the relationship between independent variables (unemployment and population) with dependent variables (poverty level). The results showed that the unemployment variable had a positive and insignificant effect on the level of poverty, meaning that the higher the unemployment rate, the higher the poverty rate. While the variable population has a negative and significant effect on poverty, meaning that the more population, the lower the poverty rate. Keywords: Unemployment, Population, Poverty.